(untitled) (World Bulletin of Education and Learning, 2025)
Speaking proficiency is widely regarded as the most challenging skill for adult learners of English as a second language (ESL). Although many adult learners possess substantial grammatical knowledge and receptive language skills, they frequently struggle to communicate fluently and confidently in real-life situations. This discrepancy between knowledge and performance is largely attributed to affective factors such as anxiety, fear of negative evaluation, limited opportunities for authentic interaction, and the dominance of form-focused instruction. Task-Based Learning (TBL) has emerged as a pedagogical approach that prioritizes meaningful communication through real-world, goal-oriented tasks. This article presents a comprehensive and in-depth analysis of Task-Based Learning in teaching speaking to adult ESL learners. It explores theoretical foundations, adult learner psychology, task design principles, instructional stages, assessment practices, classroom challenges, and pedagogical implications. The study argues that Task-Based Learning provides optimal conditions for developing fluency, confidence, and communicative competence when systematically implemented in adult ESL contexts.